Inspiratory Muscle Training to Improve Activity Tolerance in Heart Failure Patients - Amanah, Dinny Atin; Nurachmah, Elly; Nova, Prima Agustia (Media Keperawatan Indonesia, 2023)
Characteristic of heart failure patients is decreased activity tolerance which is defined as a decreased capacity to carry out activities accompanied by symptoms of dyspnea and/or significant fatigue. This study aimed to determine whether Inspiratory Muscle Training (IMT) can improve activity tolerance in heart failure patients. A systematic review design with the PICO (Population, Intervention, Comparation, and Outcome) approach has been arranged based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guideline. Articles were collected through the online database ClinicalKey Nursing, EBSCOhost, Oxford Journals, ProQuest, Sage Journals, ScienceDirect, Scopus, and SpringerLink. Articles with Randomized Controlled Trial (RCT) and quasi experimental design in English were included. Quality of the article was assessed using JBI Critical Appraisal Checklist. There were seven research articles that met the criteria in this study. Those studies show that IMT can increase activity tolerance in heart failure patients. IMT can be applied as a single intervention or in combination with other interventions. Interventions that can be combined with IMT include Cardiac Rehabilitation (CR), Peripheral Muscle Training (PMT), or Functional Electrical Stimulation (FES) programs.